Dokumenty (wybór Davida Rybaka) / Documents (selected by David Rybak) - David RYBAK (Sztuka i Dokumentacja)
Being a revised fragment of a dissertation created in 2011, under the direction of Didier Semin, at the National School of Fine Arts in Paris, this article looks at Ad Reinhardt's youthful graphic productions, particularly his press cartoon drawings produced for the Columbia Jester between 1932 and 1935, and for the magazine New Masses from 1936 until its disbandment in 1946. It is this ‘semi-secret’ story, to use the words of Robert Storr, that we are telling here. These drawings, whose reproductions were for a long time difficult to find, reveal many facets of Reinhardt's life and commitments. During his studies, far from being simply an occasional illustrator, he was, in fact, one of the key activists on the campus of the Columbia University in New York – taking the helm of a student magazine, the Columbia Jester, after the latter had censored him; becoming independent and elected, with an anti-fraternities program, to the student board; and, finally, being a member of the National Student League when it was organizing its strike against War (Students fight war, a demonstration in 1934, as well as a publication, in 1935, with its cover designed by Reinhardt). These early productions were followed by his collaboration with the weekly New Masses, an American far-left newspaper, published between 1926 and 1948. While he continued his studies and began to paint, he published numerous drawings there, most of them under pseudonyms. Apart from shedding some more light on Reinhardt, these drawings remain valuable documents of service to the analysis and comprehension of American Marxist thought during the thirties and forties. In the article we are particularly interested in the way Roosevelt's foreign policy was treated before 1941 and Nazi Germany's entering the war against the Soviet Union. The article invites us to restore the intellectual and political context to the analysis of Reinhardt's work and its paradoxical gaze, which testifies to both profound radicalism and a fair share of humour.